ANALISIS KETERAMPILAN PEMECAHAN MASALAH SISWA BERBANTUAN ARTIKEL SOCIO-SCIENTIFIC ISSUE PADA MATERI ENERGI ALTERNATIF - Denella Patrycia Sahertian; Siti Nurul Hidayati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
The aim of this study is to analyze student’s problem-solving skills using socio-scientific issue (SSI) article on renewable energy. The type of research used is quantitative with descriptive method. There are 30 students of class VII-E SMP Negeri 33 Surabaya as the subject. The instrument of this study is problem-solving skills test sheet and response questionnaire sheet. The data analysis technique of this study are analysis of the results of socio-scientific issue (SSI) article validation, analysis of the problem-solving skills, and analysis of the response questionnaire. The result of this research shows the average score on each problem-solving stage. It consist of: (1) the identifying problem stage is very skilled category with score 87; (2) the setting goal stage is skilled category with score 74; (3) the planning solution stage is skilled category with score 79; (4) the determining solution stage is very skilled category with score 86; and (5) the reviewing stage is skilled category with score 70. The problem-solving skills of class VII-E SMP Negeri 33 Surabaya as a whole has a score is 79 with skilled category. The learning process with using socio-scientific issue (SSI) article gets a positive response from students, the avarage percentage of student respon is 86% categorized very well. The suggestion for this research is to provide more detailed instructions at each stage of problem-solving.